2020
DOI: 10.1029/2019jg005505
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Variability of Dissolved Organic Carbon, Solutes, and Suspended Sediment in Disturbed Low Arctic Coastal Watersheds

Abstract: Climate change in the Arctic leads to permafrost degradation and to associated changes in freshwater geochemistry. There is a limited understanding of how disturbances such as active layer detachments or retrogressive thaw slumps impact water quality on a catchment scale. This study investigates how permafrost degradation affects concentrations of dissolved organic carbon (DOC), total dissolved solids (TDS), suspended sediment, and stable water isotopes in adjacent Low Arctic watersheds. We incorporated data o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 57 publications
(87 reference statements)
1
17
1
Order By: Relevance
“…We measured discharge using a cutthroat flume equipped with a U20 Onset Hobo level logger in Ice Creek West. Discharge data at 30 min intervals are available from 15 May 2016 and at 5 min intervals after 22 July 2016 (Coch et al, 2018(Coch et al, , 2020. In Ice Creek East, discharge was deter-4538 C. Coch et al: Comparing low and high Arctic DOM characteristics Table 1.…”
Section: Field Methods and Hydrochemistrymentioning
confidence: 99%
See 4 more Smart Citations
“…We measured discharge using a cutthroat flume equipped with a U20 Onset Hobo level logger in Ice Creek West. Discharge data at 30 min intervals are available from 15 May 2016 and at 5 min intervals after 22 July 2016 (Coch et al, 2018(Coch et al, , 2020. In Ice Creek East, discharge was deter-4538 C. Coch et al: Comparing low and high Arctic DOM characteristics Table 1.…”
Section: Field Methods and Hydrochemistrymentioning
confidence: 99%
“…The island is situated in the zone of continuous permafrost with ground ice content between 30 % and 60 % for the entire island. Physical permafrost degradation typically occurs in the form of retrogressive thaw slumps (Lantuit and Pollard, 2008) and active layer detachments (Coch et al, 2020). Ramage et al (2019) reported mean active layer depths of 52.2 ± 20.2 cm.…”
Section: Study Areamentioning
confidence: 99%
See 3 more Smart Citations